FOREIGN EXPERIENCE IN REGULATING THE PUBLIC PROCUREMENT SYSTEM - Mukhtar, Y.; Toluev, Y. (Farabi Journal of Social Sciences, 2021)
The relevance of this research topic lies in the fact that public procurement requires in-depth consideration and comprehensive analysis, including the scientific and methodological level of analysis. The use of special legal documents in public procurement and the specific procedure for the execution of these documents is not a factor in the full understanding of this direction, including the economic assessment of the entire process. An economic and statistical approach using system analysis is required, which was used by the authors of the scientific article as the proposed research methodology. One of the main parts of the progressive process of commodity exchange in the economies of the analyzed countries is the mechanism for building public procurement. Currently, the problem of material and technical support of public needs in developed countries is solved as a result of logistics processes in the system of public procurement through the acquisition and supply of goods, works, and services, tangible and intangible resources. The article submits a review of foreign experience in building a public procurement system with special features characteristic of this region of the world, presented as an object of research. Country aspects in the object under study and allowed the authors to formulate the relevant main results and conclusions concerning various parties in the public procurement system, which determined the further strategy to improve the procurement system of the government and international integration union. Key words: public procurement (PP), regulation of the public procurement system, government orders, entrepreneurship, international regional institutions, regulation of the public procurement system, procurement, USA, European Union (EU), Poland, Germany, World Bank.